Earthquakes from a radiological perspective: what is demanded from the radiologists, and what can we do? A pictorial review - Aydin, Sonay; Kazci, Omer; Ece, Bunyamin; Kantarci, Mecit (Galenos Yayinevi, 2024)
Earthquakes are among the most destructive and unpredictable natural disasters. Various diseases and ailments, such as bone fractures, organ and soft-tissue injuries, cardiovascular diseases, lung diseases, and infectious diseases, can develop in the aftermath of severe earthquakes. Digital radiography, ultrasound, computed tomography, and magnetic resonance imaging are significant imaging modalities utilized for the quick and reliable assessment of earthquake-related ailments to facilitate the planning of suitable therapy. This article examines the usual radiological imaging characteristics observed in individuals from quake-damaged regions and summarizes the strengths and functionality of imaging modalities. In such circumstances, where quick decision-making processes are life-saving and essential, we hope this review will be a practical reference for readers.
Keywords: radiology information system; R895-920; embolism; disasters; Disasters; Radiography; Medical physics. Medical radiology. Nuclear medicine; Fractures, Bone; crush injuries; emergencies; Radiologists; Emergency Radiology - Review; Earthquakes; Humans; compartment syndromes; multiple trauma; earthquakes; 3. Good health